Sleep Quality Levels and Academic Performance Among Secondary School - Sidek, Nabila; Kamal, Azlan Ahmad; Rahman, Zarizi Ab (Universitas Negeri Semarang (UNNES) in cooperation with ACPES (ASEAN Council of Physical Education and Sport), 2024)
This study investigates the link between the quality of sleep and the academic performance of secondary students in SMK Seksyen 18 Shah Alam. Using a quantitative research approach, data was gathered through surveys that employed The Pittsburgh Sleep Quality Index (PSQI) to evaluate sleep quality over a one-month period. The research sample consisted of 241 students, selected through purposive sampling. The study's results revealed a significant association between sleep quality and academic performance, underscoring the necessity for interventions aimed at improving students' sleep routines and overall educational outcomes. To sum up, this research underscores the vital role of restful sleep in enhancing the academic success of students and suggests the importance of promoting healthier sleep habits among high school students.